Penerapan Metode PDM dan PERT Pada Proyek Hotel Kelapa Gading Kota Jakarta - Yulianto, M Rizky Eko; Beatrix, Michella (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Construction project delays in Indonesia remain a critical issue, as indicated by more than 40% of projects experiencing time deviations, including the Kelapa Gading Hotel Construction Project, which recorded a delay of 1.962% in the 16th week, with planned progress of 17.589% and actual progress of 15.627%. This condition indicates that the scheduling methods used have not been able to adequately accommodate uncertainty in activity durations. This study aims to analyze project scheduling using the Precedence Diagram Method (PDM) and the Program Evaluation and Review Technique (PERT) to evaluate project duration, identify critical activities, and assess the probability of project completion. The results show that the project duration based on the PDM method is 423 days, which is 10 days longer than the initial plan of 413 days. The PERT analysis indicates significant variation in activity duration, with a probability of project completion within 413 days of 19.49%, increasing to over 99% at approximately 450 days. Therefore, the integration of PDM and PERT methods can improve scheduling accuracy and support more effective project time control.